Touching the writing. The body in Henri Michaux’s graphical work and 'Saisir’s' case for a 'rhetoric of the stroke' - Romero González, Arantxa (Escritura e Imagen, 2019)
The problem of the writing’s body is one of the most important entrances to approach tothe strokes of the poet-painter Henri Michaux. Thus, the present article proposes an unprecedentedreflective look, alongside Jacques Derrida and Jean-Luc Nancy’s ideas that touches the writing itself.Accordingly, we analyze through the theoretical texts and works of the mentioned artist his beginningaround the figurative body and how he passes to write the body itself with ideographic routes where thestroke as a preliteral writing (Derrida’s term) is exploited. In this sense, we propose a close reading ofthe graphic book Saisir as a paradigmatic case of the writing body’s research from the centrality thatthe touch holds in his work.
Keywords: Henri Michaux; writing; Jacques Derrida; touch; Jean-Luc Nancy; drawing; stroke